(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
Irving Fisher was an American economist who is known as one of the pioneers of modern economic thought. Fisher’s philosophical economic thinking is rooted in the idea of ??the relationship between macro and microeconomics, the importance of price stability, and the influence of the economy on human welfare. The method used in this study is a literature review and analysis, through an analysis of Irving Fisher’s writings and his philosophical thoughts. This article examines Fisher’s economic philosophy by highlighting his contributions to the quantity theory of money, interest rate analysis, and the relationship between economic health and productivity